2017
DOI: 10.1063/1.4978497
|View full text |Cite
|
Sign up to set email alerts
|

Wetting at the nanoscale: A molecular dynamics study

Abstract: A novel method to calculate the solid-liquid contact angle is introduced in this study. Using the 3D configuration of a liquid droplet on a solid surface, this method calculates the contact angle along the contact line and provides an angular distribution. Although this method uses the 3D configuration of liquid droplets, it does not require the calculation of the 3D density profile to identify the boundaries of the droplet. This decreases the computational cost of the contact angle calculation greatly. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 52 publications
3
63
1
Order By: Relevance
“…It has been stated previously that the droplet size impacts the contact angle [68]. For systems similar to the one investigated here, it has been found that increasing droplet sizes results in narrower contact angle distributions [64]. Furthermore, fluctuations in the droplet shape decreases for larger droplets.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…It has been stated previously that the droplet size impacts the contact angle [68]. For systems similar to the one investigated here, it has been found that increasing droplet sizes results in narrower contact angle distributions [64]. Furthermore, fluctuations in the droplet shape decreases for larger droplets.…”
Section: Discussionsupporting
confidence: 70%
“…For the system with the original energy well depth ε 0 , the water contact angle is calculated to be 73.49 ± 3.44 • . The contact angle of graphite and graphene has been studied by atomistic simulations previously, with reported contact angles ranging from 83 • for graphite [64] to a predicted 90-95 • for graphene [65]. Although the contact angles obtained in this study are below these values, the studies in literature used the SPC/E forcefield, which may give different contact angle values.…”
Section: Simulation Detailsmentioning
confidence: 81%
See 1 more Smart Citation
“…Other applications of the Helfrich expansion include elastic properties of biological membranes, 15,29 highly curved films, 16 and wetting at the nanoscale. 30,31 Previous literature has dealt almost exclusively with one-component droplets; in reality, however, most interfaces contain several components. This paper deals with the curvature dependence of the surface tension for multicomponent fluids, which is conceptually more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the driving pressure is needed to be increased to around 3.5 times in order to reach just nearly 20%. Normally, high velocity and high driving pressure can be used to prevent nozzle clogging but it is not effective in this case because wetting behavior at nanoscale . Thus, the chemical effect of surfactant is superior to the mechanical effect on deposit reduction because only 1% of surfactant can reach 60% as previously discussed in Figure .…”
Section: Resultsmentioning
confidence: 99%